DREAMpy - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The economic assessments of agriculture projects can become a powerful tool to effective public spending and priority setting. DREAMpy is an open source user-friendly software that allows analysts to evaluate agricultural R&D projects. This tool is based on an economic surplus partial equilibrium model (Alston et al. 1995) and builds on the IFPRI 1995 DREAM (Dynamic Research EvaluAtion for Management) software package that has been widely used around the world. Users now can download the DREAMpy software package and run it directly without having to install any additional software on their Windows computers. DREAMpy built-in Excel input worksheets guide users, allowing them to run evaluations with different degrees of complexity. DREAMpy was developed in collaboration with Vitamin Software, as a component of BIORAPP, a project led by IFPRI’s Program for Biosafety Systems (PBS). BioRAPP was funded by the Bill and Melinda Gates Foundation and the U.S. Agency for International Development.